Bridging the compliance gap: A literature review on money laundering challenges and the role of frontline officers in Malaysian commercial banks - Vijayaraj R Kanniah; Izaan Jamil; Nelson Lajuni; Mohd Rahimie Abd Karim; Zaiton Osman; Azmi Majid; Yahyah Sidek (Asian Scholars Network, 2025)
Money laundering remains a pressing concern in the financial sector, especially within commercial banks. Despite the presence of detailed regulatory frameworks such as the Anti-Money Laundering, Anti-Terrorism Financing and Proceeds of Unlawful Activities Act 2001 and the Financial Services Act 2013, many financial institutions still face considerable penalties for failing to comply. This paper offers a thorough review of the existing research on money laundering in Malaysia, focusing on key cases, regulatory measures and the challenges faced by institutions. A notable gap exists between following policies and the actual awareness of frontline bank officers, who act as the first point of contact with customers. Although Malaysia has made progress in strengthening its anti-money laundering system, research remains limited regarding how prepared and effective these officers are. The paper emphasizes the need for targeted training, improved internal controls and clearer instructions from regulators to help detect and report suspicious transactions more effectively. To protect the integrity of Malaysia’s financial system and sustain public trust, it concludes with suggestions for enhancing the role of frontline personnel.